ANALISIS PENERAPAN STANDART AKUNTANSI KEUANGAN ENTITAS MIKRO, KECIL DAN MENENGAH (SAK EMKM) DALAM PENYUSUNAN LAPORAN KEUANGAN PADA UMKM (Studi Kasus Usaha Mikro Kecil dan Menengah Kecamatan Ngantang) (e_Jurnal Ilmiah Riset Akuntansi, 2022)
Micro, small and medium enterprises are industrial or household businesses with limited human resources and expertise. The main problem is that the preparation of financial statements based on financial accounting standards for SMEs has not been realized. This includes annual financial statements, income statements, and memos. The contribution of SMEs to the country's economic growth is very important. To that end, the Indonesian Institute of Accountants has developed Financial Accounting Standards for Micro, Small and Medium Enterprises as Special Financial Accounting Standards for Micro, Small and Medium Enterprises to assist stakeholders in Micro, Small and Medium Enterprises. The case study of micro, small and medium enterprises in Ngantang Regency includes 5 economic actors with interviews and documents. The results of this study conclude that MSMEs have not implemented their financial records in accordance with MSME accounting standards. Some business owners record income and expenses only to the best of their ability and most do not keep financial records.Keywords: Application of Financial Accounting Standards for Micro, Small and Medium Entities in Micro, Small and Medium Enterprises